Gold uptake from dilute chloride solutions by a Lewatit TP 214 and activated rice husk - Aktas, Serdar; Morcali, M. Hakan (Elsevier BV, 2011)
Abstract The present work investigates gold uptake using a commercial resin, Lewatit TP 214, and rice husk, agricultural waste, from synthetically prepared, dilute gold chloride solutions with 100 ppm gold (Au3+) and provides a comparison between these two sorbents. The effects of the different uptake parameters on gold uptake (%) were studied in detail. Before the rice husks were activated, the gold uptake (%) was poor in comparison with Lewatit TP 214. However, after the husk was activated at 1000 °C under an argon atmosphere, the gold uptake (%) increased fourfold. The gold uptake (%) increased with increasing sorbent dosage, contact time, and temperature. Additionally, the gold uptake by activated rice husks and Lewatit TP 214 is an intermediate-controlled process with activation energies of 28.44 and 26.41 kJ/mol, respectively. The XRD patterns revealed that the gold was in its metallic form. The gold uptake capacities for the activated rice husk and Lewatit TP 214 were 93.3 and 109.6 mg Au per gram, respectively.